Foreign trade elasticities for industrial countries: 1990-2012 - Via, Alessia (My University, 2012)
Global imbalances are a threat for the global economy and disorderly adjustments as well as errors in forecasting or in the interpretation of results can yield negative outcomes. Focusing on export price elasticities, I argue that the constant complaints about the underbidding behavior of some economies by their major trading partners can disclose further outcomes useful for the study of international interdependencies and trade patterns. Therefore, my main purpose is to provide an overall view of the previous research carried out on trade elasticity issues and to analyze the implications of global current account imbalances. For what concerns exports, price elasticities estimated in the previous literature feature a high variability with values that range from -0.14 to -3.13. Some of these results, in particular, can be considered controversial with respect to one side of the current debate and cause complexity in their interpretation. In order to accomplish the analysis, I apply a cointegration model in an error correction framework to estimate export elasticities covering the period from 1990 to 2012 for countries that represent both surplus and deficit sides of the current debate: Italy, Germany, France, USA, UK, Japan and China. Using these estimates, in combination with the prevalent macroeconomic forecasts related to the issue, I will illustrate how variations in exchange rates and in income can produce effects on exports with the provision of estimates of export price and income elasticities.
Dottorato di ricerca in Scienze economiche e aziendali, XXV ciclo, a.a. 2009-2012
Keywords: Foreign exchange rates; Elasticity (Economics)